Incidence and characteristics of nosocomial influenza in a country with low vaccine coverage. Issue 4 (August 2020) - Luque-Paz, D.; Pronier, C.; Bayeh, B.; Jouneau, S.; Grolhier, C.; Le Bot, A.; Bénézit, F.; Thibault, V.; Tattevin, P.
Summary: Background: Influenza vaccination coverage is low in France, in at-risk patients and in healthcare workers. Aim: We aimed to estimate the incidence of nosocomial influenza, its characteristics and outcome. Methods: During one influenza season, we retrospectively evaluated all cases of documented influenza. Inpatients with symptoms onset ≥48 h after admission were enrolled. Data were collected on a standardized questionnaire. Results: From November 2017 to April 2018, 860 patients tested positive for influenza by polymerase chain reaction analysis on a respiratory sample. Among them, 204 (23.7%) were diagnosed ≥48 h after admission, of whom 57 (6.6% of all influenza cases) fulfilled inclusion criteria for nosocomial influenza: 26 women and 31 men, median age 82 years (interquartile range, 72.2–86.9). Twenty patients (38.6%) had recently (<6 months) received the seasonal influenza vaccine. Median time between admission and symptoms onset, and between symptoms onset and diagnosis were, respectively, 11 days (7–19.5) and 29 h (15.5–48). Influenza was mostly acquired in a double-bedded room ( N  = 39, 68.4%), with documented exposure in 14 cases. Influenza B virus was more common in nosocomial (46/57, 80.7%), than in community-acquired cases (359/803, 44.6%), P< 0.001. Mortality rate at three months was 15.8% ( N  = 9). Incidence of nosocomial influenza was estimated at 0.22 per 1000 hospital-days during the study period. Conclusion: Nosocomial influenza is not rare in elderly inpatients, and may have severe consequences. Influenza B virus was over-represented, which suggests higher transmissibility and/or transmission clusters.